PERANCANGAN ARSITEKTUR ENTERPRISE PADA LEMBAGA MI PUTRI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH MENGGUNAKAN METODE TOGAF ADM - Fatimah Isa Auliya; Septi Camelia Ulfa; Akhlis Munazilin (CV. Denasya Smart Publisher, 2026)
The rapid development of information technology necessitates that educational institutions have integrated and efficient data management systems. At MI Putri Pondok Pesantren Salafiyah Syafi’iyah, many administrative and academic activities are still conducted manually or through separate applications, resulting in data duplication and a slow information flow. This study designs an enterprise architecture using the TOGAF ADM framework as a blueprint for developing an integrated information system. Data were collected through observation, interviews, and document analysis to understand current conditions and needs. The design includes business, data, application, and technology architectures, supported by SWOT analysis and an implementation roadmap. The results indicate that MI Putri requires a centralized system to integrate key processes, including admissions, attendance, assessments, and administration. The proposed architecture provides clear guidance for building an efficient, adaptive, and sustainable information system that improves service quality and strengthens information management.